Down-conversion of short-wavelength radiation in LBO crystal - Kononova, Nadezda G.; Kokh, Alexander E.; Kokh, Konstantin A.; Lanskii, Grigory V.; Losev, Valery F.; Svetlichnyi, Valerii A.; Andreev, Yury M. 1946- (Russian physics journal)
Comparative model analysis of the possibilities of down-conversion into the terahertz (THz) frequency range of radiation of all-solid-state femtosecond Ti:Sapphire laser systems and hybrid systems based on the same type lasers and equipped with amplifiers on XeF(C-A) and XeCl(C-A) molecules of excimer gases with harmonic generators on nonlinear LBO crystals is performed. It is established that when the crystal is cooled to a temperature of 80 K, the coefficient of optical losses in the frequency range from 0.2 to 1.5 THz linearly decreases in the direction of the X axis by 5-6 times down to 0.1-0.2 cm-1. It is shown that the use of hybrid laser systems as pumping sources will allow the power of generated THz pulses to be increased from 3.5 to 20 times. © 2016, Springer Science+Business Media New York.